2019
DOI: 10.1093/swr/svz003
|View full text |Cite
|
Sign up to set email alerts
|

Building Knowledge to Support Human Service Organizational and Management Practice: An Agenda to Address the Research-to-Practice Gap

Abstract: Leaders of human service organizations (HSOs) face significant pressures from policymakers and funders to justify practices and ensure successful outcomes, an issue that has implications for social work practitioners and evidence-informed management practice. Although empirical research has advanced understanding of the factors that improve human service effectiveness and organizational improvement, considerable research-to-practice gaps exist and the use and translation of knowledge into regular management pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In scholarly debates about the development of the social work profession, implementation science has been introduced as a field of inquiry that, due to its applied nature, can help to create stronger bidirectional ties between research and practice and thereby enhance the relevance and quality of social work as well as its capacity to address societal problems (Bunger & Hall, 2019; Cabassa, 2016; Gehlert et al, 2017). A central point of attention in these debates is the connectedness of research and practice, with learning collaboratives (Bunger et al, 2016; Stephens et al, 2014), partnerships between academic and social and human service organizations (McBeath et al, 2019; Palinkas et al, 2017), and the research-minded practitioner (DePanfilis, 2014; Liedgren, 2020) being among the suggested solutions for how to create closer linkages between these domains. With this review, we add a further potential solution to this list—the ISP—and propose for it to be considered as a role that can actively bridge the research–practice gap in social work and help human and social service organizations to establish and facilitate the adaptive learning required not only to implement ready-made RSIs but also to apply evidence in the design and improvement of local practice (Mosley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In scholarly debates about the development of the social work profession, implementation science has been introduced as a field of inquiry that, due to its applied nature, can help to create stronger bidirectional ties between research and practice and thereby enhance the relevance and quality of social work as well as its capacity to address societal problems (Bunger & Hall, 2019; Cabassa, 2016; Gehlert et al, 2017). A central point of attention in these debates is the connectedness of research and practice, with learning collaboratives (Bunger et al, 2016; Stephens et al, 2014), partnerships between academic and social and human service organizations (McBeath et al, 2019; Palinkas et al, 2017), and the research-minded practitioner (DePanfilis, 2014; Liedgren, 2020) being among the suggested solutions for how to create closer linkages between these domains. With this review, we add a further potential solution to this list—the ISP—and propose for it to be considered as a role that can actively bridge the research–practice gap in social work and help human and social service organizations to establish and facilitate the adaptive learning required not only to implement ready-made RSIs but also to apply evidence in the design and improvement of local practice (Mosley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…From an organizational perspective, this can also include providing additional fiscal and human capital resources that can reinforce operational mandates (Brownson et al, 2018). Practitioners often encounter numerous challenges that arise because of the complexity of adopting and implementing interventions—particularly interventions that are new to them (Domlyn et al, 2021; Kenworthy et al, 2023; McBeath et al, 2019). Motivational barriers can include being underfunded or overburdened to conduct new activities, incongruities with respect to provider-client expectations, and lack of leadership or managerial support.…”
Section: Complexities Of Implementation Supportmentioning
confidence: 99%
“…Similarly, researchers in academic settings aim to investigate mentoring programmatic processes and the role of mentoring on youth outcomes. Research-to-practice partnerships (RPP) are one way for mentoring practitioners and researchers to broadly address issues within the field of youth mentoring and development (McBeath et al, 2019). RPPs are defined as ongoing relationships between practitioners and researchers that are characteristic of mutuality and strategic partnership aimed at investigating problems of practice (Coburn et al, 2013).…”
mentioning
confidence: 99%